EKSPLOITASI TENAGA KERJA DI INDUSTRI MAKANAN RINGAN: STUDI KASUS PT ALPEN FOOD INDUSTRI (AFI) - Hidayat, Amelia; Sekar Arum, Dewi; Nurisma, Irfa (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
PT Alpen Food Industry (AFI), the largest ice cream producer in Indonesia, is widely known with more than 80,000 outlets throughout the country. However, behind this success, this company is suspected of being involved in labor exploitation practices which have caused tension with its workers. The strike which lasted for two weeks and demonstrations by workers occurred in response to alleged violations of workers' rights, including unilateral termination of employment (PHK) which was deemed not in accordance with applicable employment procedures. The company denied these allegations by stating that the layoffs had been carried out in accordance with existing guidelines. to analyze the causes and impacts of employment problems at PT AFI. The research results show that this conflict is caused by poor communication between the company and workers, as well as the company's failure to implement adequate business ethics, especially in protecting labor rights. Apart from that, this research also identified violations of labor standards which should be part of corporate social responsibility. In its conclusion, this paper proposes the need to sharpen labor regulations and strengthen corporate ethics to encourage the creation of harmonious working relationships.